Karakterisasi Material Hanger Panjat Tebing - Kwintarini, Widiyanti; Sonawan, Hery; Alqurin, Wais (POROS, 2023)
The Rock climbing hangers function as anchors for safety when climbing and are usually used for cliff surfaces that have few natural anchors. The tests that will be carried out in this research are chemical composition testing, hardness testing and metallographic testing. Testing the chemical composition of materials aims to find out what alloys are in imported and local rock climbing hangers. In the material composition test results, the imported rock climbing hangers are Austenitic Stainless Steel 304, because they contain 18.49% Chromium (Cr) and 7.92% Nickel. The local rock climbing hangers are low carbon steel, because they contain 0.056% Carbon © elements. The hardness value of imported rock climbing hangers is greater, namely 292 HVN, compared to local rock climbing hangers which have a hardness value of 136 HVN. Local rock climbing hangers are low carbon steel so they are dominated by the ferrite phase and there is a small amount of pearlite phase. Meanwhile, the imported rock climbing hangers are Austenitic Stainless Steel 304 which have undergone a cold rolling process. The tensile test results show that the imported hanger has a stress value of 7655 N or 729 MPa, higher than the local hanger with a stress value of 2826 N or 259 MPa